2013
DOI: 10.1111/1460-6984.12072
|View full text |Cite
|
Sign up to set email alerts
|

The ‘robustness’ of vocabulary intervention in the public schools: targets and techniques employed in speech–language therapy

Abstract: This study examined vocabulary intervention-in terms of targets and techniques-for children with language impairment receiving speech-language therapy in public schools (i.e., non-fee-paying schools) in the United States. Vocabulary treatments and targets were examined with respect to their alignment with the empirically validated practice of rich vocabulary intervention. Participants were forty-eight 5-7-year-old children participating in kindergarten or the first-grade year of school, all of whom had vocabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 64 publications
(157 reference statements)
2
18
0
Order By: Relevance
“…coincidence, industrious, fortunate, introduce. While more low-frequency subject-specific words may be specifically taught in the classroom (e.g., peninsula, isotope, stanza), these crosscurriculum words are used across topics in schools but may not be taught explicitly (Beck et al 2002, Justice et al 2014. Vocabulary interventions should target these cross-curriculum words, given their potential impact on success within the classroom (Justice et al 2014).…”
Section: Importance Of Cross-curriculum Vocabulary Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…coincidence, industrious, fortunate, introduce. While more low-frequency subject-specific words may be specifically taught in the classroom (e.g., peninsula, isotope, stanza), these crosscurriculum words are used across topics in schools but may not be taught explicitly (Beck et al 2002, Justice et al 2014. Vocabulary interventions should target these cross-curriculum words, given their potential impact on success within the classroom (Justice et al 2014).…”
Section: Importance Of Cross-curriculum Vocabulary Learningmentioning
confidence: 99%
“…Evidence for the effectiveness of vocabulary intervention is well established during the preschool and primary school years (Best et al 2006, Lubliner and Smetena 2005, Justice et al 2014, Marulis and Neuman 2010, Steele and Mills 2011 with emerging evidence for secondary school-aged children, particularly using whole-class approaches (Lesaux et al 2010, Snow et al 2009). These studies typically involve children acquiring relevant information about different aspects of a word (including semantic, phonological, morphological, grammatical and orthographic) in order to establish clear lexical representations (Stackhouse and Wells 2001).…”
Section: Principles Of Teaching Cross-curriculum Vocabularymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, all participating children in this study were those who had been clinically identified as requiring speech-language services. The SLPs forwarded study and consent information to parents of potentially eligible children, as well as screening information regarding children's hearing screening, home language and concomitant disabilities (see Justice et al 2014 for complete study recruitment procedures). Preference for study enrolment was for children with a primary LI; however, a small proportion of the study participants were additionally diagnosed with autism (n = 10), attention-deficit hyperactive disorder (n = 18), developmental delay (n = 10), epilepsy (n = 2), and traumatic brain injury (n = 1).…”
Section: Participantsmentioning
confidence: 99%